ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT. BLUE BIRD TBK - Rakhmanita, Ani (Aksara Public, 2018)
This study aimed to analyze the financial performance of PT. Blue Bird Tbk, based Ratios Liquidity, Solvency, Activity and Profitability in 2014 until 2016. This study used quantitative descriptive approach. The results showed that: (1) The liquidity ratio to measure the ability of PT Blue Bird Tbk in meeting short-term obligations through indicators Current Ratio and Cash Ratio is in the category of performance "less good", (2) Solvency Ratio to measure the ability of firms to pay long-term liabilities if the company is liquidated, through indicators Debt to Equity Ratio (DER) and Debt to Total Asset Ratio (DAR) showed a tendency to decrease year after year. (3) Ratio Activity through indicator Total Assets Turn Over, its shows the tendency The Activity Ratio through the Total Asset Turn Over indicator shows a tendency to be inefficient. (4)Ratios Profitability through indicators Gross Profit Margin (GPM), Return on Equity (ROE), Return on Asset (ROA) and Net Profit Margin (NPM), it shows the tendency continues to decline from year to year. It can be concluded that all four indicators below the average industry standard, so it can be concluded that the financial performance. PT. Blue Bird Tbk is in the category of "less good".